THE OCCURRENCE AND SOURCE EVALUATION OF POLYCYCLIC AROMATIC HYDROCARBONS IN URBAN ATMOSPHERE USING MOSS AS BIOMONITOR AND GC-MS ANALYSIS - ROTARU, Andreea; REIZER, Edina; PĂNESCU, Vlad; POP, Sorin; BELDEAN-GALEA, Mihail Simion (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are part of the persistent organic pollutants (POPs) class. The most harmful PAHs are generated during the incomplete combustion of organic material. European legislation has recommended the use of bioindicators to estimate the impact of PAHs on the ecosystem. The aim of this work was to investigate the occurrence of atmospheric PAHs in 14 urban areas in Romania, using moss as bioindicator. The pollution emission sources, applying diagnostic ratios, were also evaluated. The PAHs were analyzed by gas chromatography-mass spectrometry (GS-MS). This study showed the presence of PAHs in moss samples in concentrations which are dependent on the sampling zone, ranging from 2.7 to 394 ng g-¹. The cities with the highest amounts of total PAHs were found within the Carpathian arch, while the cities situated in the western part of the country had the lowest amounts. The FLA/(FLA+PYR) and FL/(FL+PYR) ratios indicate both the diesel emission source, fossil fuels combustion source and wood or coal combustion source which may come either from traffic, industrial activities, centralized heating systems, or from other type of industry.